(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Operational performance in Kenyan public hospitals remains a persistent managerial and policy concern, particularly due to frequent medicine stock-outs, delayed replenishment cycles, and service delivery inefficiencies. These challenges are closely associated with weak supply chain responsiveness within public healthcare procurement and supplier systems. This study examines the relationship between supply chain responsiveness, operationalized through Just-in-Time (JIT) inventory practices, and operational performance in public hospitals in Siaya County, Kenya. The study is anchored on the Resource-Based View (RBV) and Network Perspective Theory, which explain how internal replenishment capabilities and inter-organizational supply chain relationships jointly influence hospital performance outcomes. A cross-sectional survey research design was adopted involving 84 respondents drawn from procurement, pharmacy, stores, and hospital administration departments across six public hospitals. Data were collected using structured questionnaires and interview guides. Reliability testing yielded Cronbach’s alpha coefficients exceeding 0.80, while the content validity index exceeded 0.70, confirming the robustness of the measurement instruments. Descriptive statistics summarized institutional practices, while correlation and regression analysis examined relationships between variables. The findings reveal a strong and statistically significant positive relationship between Just-in-Time inventory practices and operational performance (β = 0.738; p < 0.05). The regression model explains 79.1% of the variation in hospital operational performance (R² = 0.791), indicating that responsive replenishment practices significantly contribute to improved medicine availability, reduced stock-outs, and enhanced service delivery efficiency. The study concludes that strengthening supply chain responsiveness through responsive procurement systems, flexible supplier relationships, and shortened replenishment lead times is essential for improving operational outcomes in Kenyan public hospitals. Policy recommendations emphasize the need for improved coordination between hospitals and national medical supply agencies, enhanced procurement flexibility, and the integration of digital logistics management systems to strengthen healthcare supply chain responsiveness.